2013
DOI: 10.1080/17429145.2013.791379
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous glycinebetaine and humic acid improve growth, nitrogen status, photosynthesis, and antioxidant defense system and confer tolerance to nitrogen stress in maize seedlings

Abstract: Abiotic stresses, including nitrogen stress (NS), can hamper photosynthesis and cause oxidative damage to plants. Upregulation of the antioxidative defense system and photosynthesis induced by exogenous glycinebetaine (GB) and humic acid (HA) can mitigate the inhibitory effects of NS on plants. In the present investigation, the beneficial effects of exogenously applied GB and HA were examined on growth, leaf N status, photosynthesis, lipid peroxidation, and activities of some key antioxidant enzymes in the see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…The growth inhibition induced by the simulated drought stress in this study has previously been observed in maize 24 and other plant species 5 . The reduction in the root biomass may have arisen from root respiratory inefficiency 25 , and the reductions in the shoot biomass have been reported reductions in chlorophyll content, PSII function, transpiration rates and stomatal conductance as well as by the diminished activities of key enzymes involved in carbon dioxide fixation 24 , 26 , and these effects were also observed in the present study. Interestingly, the deleterious effects of the simulated drought conditions on maize seedling growth were partly counteracted by the DCPTA pretreatment (Table 1 ).…”
Section: Discussionsupporting
confidence: 78%
“…The growth inhibition induced by the simulated drought stress in this study has previously been observed in maize 24 and other plant species 5 . The reduction in the root biomass may have arisen from root respiratory inefficiency 25 , and the reductions in the shoot biomass have been reported reductions in chlorophyll content, PSII function, transpiration rates and stomatal conductance as well as by the diminished activities of key enzymes involved in carbon dioxide fixation 24 , 26 , and these effects were also observed in the present study. Interestingly, the deleterious effects of the simulated drought conditions on maize seedling growth were partly counteracted by the DCPTA pretreatment (Table 1 ).…”
Section: Discussionsupporting
confidence: 78%
“…GB has a well-documented effect as osmoprotectant, and maintaining a better water status allows greater gas exchange levels and photosynthesis, and higher turgor driving cell expansion and shoot growth. Furthermore, GB application has been reported to increase leaf nitrogen content (Zhang et al, 2014), thus contributing to growth enhancement. Indeed, foliar application of GB resulted in higher levels of fresh biomass, due to greater tissue water content of the shoots, which can reduce the toxic effects of high levels of NaCl (Marcum & Murdoch, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…HA was reported to positively influence net photosynthesis along with enhancing chlorophyll percentage and stomatal conductance (Tahir et al, 2013). In addition, the activity of two key photosynthetic enzymes, phosphoenolpyruvate carboxylase and ribulose-1,5-bis phosphate carboxylase was enhanced in response to HA treatment (Zhang et al, 2014). Total sugars, total free amino acids and protein concentrations were increased in snap bean treated with HA (Hanafy et al, 2010).…”
Section: Effects Of Hamentioning
confidence: 99%